2019
DOI: 10.1002/adhm.201900275
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity‐Attenuated Glycol Chitosan Adhesive Inspired by Mussel Adhesion Mechanisms

Abstract: COMMUNICATION 1900275 (1 of 8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…In another study, chitosan modified with both catechol and ethylene glycol demonstrated hemostatic properties with a reduced immune response associated with catechol-modified chitosan. 165 However, glycol modification did not significantly improve the adhesive and hemostatic properties of the hydrogels when compared with the unmodified catechol-chitosan hydrogels. 148,165 In one interesting design, the surface of a needle was coated with a thin homogenous film of the partially oxidized catechol-functionalized chitosan.…”
Section: Tissue Sealant and Adhesivementioning
confidence: 87%
See 2 more Smart Citations
“…In another study, chitosan modified with both catechol and ethylene glycol demonstrated hemostatic properties with a reduced immune response associated with catechol-modified chitosan. 165 However, glycol modification did not significantly improve the adhesive and hemostatic properties of the hydrogels when compared with the unmodified catechol-chitosan hydrogels. 148,165 In one interesting design, the surface of a needle was coated with a thin homogenous film of the partially oxidized catechol-functionalized chitosan.…”
Section: Tissue Sealant and Adhesivementioning
confidence: 87%
“…165 However, glycol modification did not significantly improve the adhesive and hemostatic properties of the hydrogels when compared with the unmodified catechol-chitosan hydrogels. 148,165 In one interesting design, the surface of a needle was coated with a thin homogenous film of the partially oxidized catechol-functionalized chitosan. 166 The film thickness was around 20-26 μm depending on the needle gauge.…”
Section: Tissue Sealant and Adhesivementioning
confidence: 87%
See 1 more Smart Citation
“…The results showed that glycol CS-C significantly attenuated the immune response. However, the tissue adhesion and hemostatic ability of glycol CS-C were not dramatically improved, and it was speculated that the finding was likely due to the antibiofouling effect of the ethylene glycol group and the reduction of immune cell adhesion [ 35 ]. Although significant progress has been made in bioelectronics research in recent years, it is still challenging for self-adhesive bioelectronics to adhere to human tissues and achieve signal detection without external aids.…”
Section: Biomaterials Imitating Bivalvesmentioning
confidence: 99%
“…[3] Biomass-based nonformaldehyde adhesive substitutes with good bonding properties have been widely applied for the wood panel industry. [4] Among the many biomass-based raw materials such as lignin, [5] tannin, [6] protein, [7] starch, [8] and chitosan, [9] soy protein has become an ideal material for preparing wood adhesives due to its abundant resources, renewability, and low price; however, the low bonding strength, poor water, and mold resistance have limited its applications. [10][11][12]13] In order to enhance the performance defects of soy protein adhesives, a series of modification strategies have been used, such as the use of protein denaturation techniques, chemical crosslinking, organic or inorganic blending, and biomimetic design.…”
Section: Introductionmentioning
confidence: 99%